308 THE BROKEN HEART: A LEFT VENTRICLE FREE WALL RUPTURE IN MINOCA. (15th December 2022) - Costantino, Roberto; Leopizzi, Alessandra; Milo, Maria; Martino, Roberto; Ignone, Gianfranco
Abstract: 86 years-old man was admitted to our ICCU for chest pain with an ECG diagnosis of atrial fibrillation and inferior STEMI. He had a history of hypertension and ascending aorta aneurysm (48 mm) with no other known cardiovascular risk factor. He reported few episodes of short-duration chest pain in the last days. A fast echocardiogram excluded ascending aorta dissection and pericardial effusion but showed hypokinesia of inferolateral left ventricle wall. Urgent angiography only revealed a moderate stenosis on mid left anterior descending artery associated with slow run-off. No lesions were found on the expected culprit artery. Due to persisting chest pain and patient's history of ascending aorta aneurysm, an urgent Angio CT was performed, but unexpectedly, during the exam, the patient lost consciousness with asistolia. RCP was practised with ROSC. CT scan showed mild pericardial effusion with blushing. A free wall heart rupture was suspected by radiologist. Urgent echocardiogram revealed moderate pericardial effusion with a suggestive colour doppler systolic flow originating from an apparent hole in apical inferolateral left ventricle wall. Rapid hemodynamic failure occurred so pericardiocentesis with amine support and blood transfusions were performed. Heart team excluded urgent surgery due to extremely high operative risk related to patient's age, hemodynamic impairment and poor expected repair durability consequent to acute phase of rupture. ICCU observation was made, with liable hemodynamic stability obtained with norepinephrine infusion. In accordance with patient's family other invasive measurements were not taken. Unfortunately, the patient died the day after. Only few cases of myocardial rupture in myocardial infarction-non obstructive coronary artery disease (MINOCA) are reported in literature. Recurrent chest pain makes plaque complication/embolus resolution a reliable hypothesis. New onset atrial fibrillation might have caused an embolization in coronary artery determining transmural ischaemia, as well as coronary artery plaque rupture/ulceration might have done. Unfortunately, no further exams to exploit the underneath pathological process could be performed: Coronary intravascular ultrasound, optical coherence tomography, Cardiac Magnetic resonance would be a valid help in prognosis and future treatment.